Temperature-dependent growth rates and relative activity of extracellular hydrolytic enzymes in a tropical fungal strain of Fusarium equiseti and polar strains of Pseudogymnoascus spp. / Nor Farah Natasha Tajuddin - Nor Farah Natasha , Tajuddin (2018)

(untitled)
The relative growth rates and relative activity (RA) of extracellular hydrolytic enzymes (EHEs) in a marine-derived tropical strain of Fusarium equiseti and polar (Arctic and Antarctica) strains of Pseudogymnoascus spp. under different solid-state nutrient assays would differ across culture temperatures between 5°C and 40°C. Relative growth rates and RA indices of protease, amylase and cellulase in these strains were screened in seawater solid-state nutrient assay plates augmented with skim milk, soluble starch, or carboxylmethylcellulose with trypan blue, respectively. Fungal colony and clear zone diameters were measured in the mid-log phase of growth to calculate relative growth rates and RA indices of these EHEs in selected strains. Relative growth rate values were fitted into third-degree polynomial and Brière-2 temperature-dependent models to estimate optimum temperatures for growth (Topt) and maximum growth rates (Rmax) of the selected strains under different nutrient assays. Estimates of growth rate values from the Brière-2 model were used to calculate the temperature coefficient (Q10) and activation energy (Ea) for growth in all three fungal strains under different nutrient sources across the experimental culture temperature range. Similarly, specific growth rates in the three selected strains grown for 10 d under a liquid culture system comprised of seawater Mueller-Hinton Broth would differ across the same experimental culture temperature range. Values of Topt, Rmax, Q10, and Ea were calculated using specific growth rate values obtained from the experiment. Changes in pH over time in the culture medium were also recorded. The findings indicated that Fusarium equiseti is better adapted to utilizing higher levels of thermal energy for growth than Pseudogymnoascus spp., consistent with general definitions that classify the former as a mesophile and the latter psychrophiles. EHE activity of protease, amylase, and cellulase in the three strains corresponded to the composition and abundance of particulate organic matter in the marine environment in tropical and polar latitudes, in which all three strains showed protease and amylase activities. Only Pseudogymnoascus spp. showed no cellulase activity during growth. This may suggest Pseudogymnoascus spp. might have achieved adaptation through loss of function under environments that typically have limited cellulosic materials. Increment of pH was observed during the growth (increased biomass) of Fusarium equiseti and Pseudogymnoascus spp. in the liquid culture system, which implies utilisation of substrates through EHE activity of mainly protease and amylase were facilitated by more alkaline conditions.